Perda e fragmentação de habitat da Mata Atlântica: efeitos locais e da paisagem sobre a comunidade de rola-bostas (Coleoptera: Scarabaeinae) - Cortez, Luiz Otávio (2021)
Anthropogenic activities represent a great risk to global biodiversity. The loss and fragmentation of habitats has represented a large part of the impacts caused by human activity on biological communities. The Atlantic Forest is a biome that has historically suffered from human occupation and the consequent fragmentation process, having its vegetation cover replaced by pastures, agricultural crops, cities, and roads. This context provides us good conditions to understand the responses of communities to habitat loss and fragmentation. For this reason, this work was carried out with the aim of investigating the responses of the community of dung beetles to the variation of local and landscape conditions in a context of hyper fragmentated forest. Dung beetles are highly sensitive to environmental variations, in addition to enabling fast and low-cost sampling. Therefore, they represent an important focal group for studies that seek to assess the impacts of human activities. Regarding that, we sampled dung beetle communities in 30 landscapes in the Atlantic Forest domain through pitfalls baited with a mixture of pig and human feces. We calculated the proportion of forest cover for each landscape, forming a gradient of habitat amount. In addition, local characteristics of soil, vegetation, microclimate, and topography were also measured. It was observed that the community of dung beetles responded mainly to the local characteristics of each sampling points. Furthermore, it was observed that when separating the community into groups considering its functional traits, the community response was mainly determined by the response of small beetles, while the other groups were not greatly influenced by the measured variables. These results demonstrate the importance of considering a wide range of local and landscape features, in addition to the need for a more detailed observation of the beetle community, while dung beetles with different functional traits have been shown to have different responses to effects of forest loss and fragmentation.